Implementation of Child-Friendly School Program in Creating a Positive School Climate - Nadia Pratiwi; Rudi Hariawan; Muhammad Iqbal (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to examine the implementation of Child-Friendly School (CFS) program in creating a positive school climate at SMPN 22 Mataram. The research focuses on three aspects: planning, implementation, and evaluation of the CFS program. Using a qualitative approach with a case study design, data were collected through semi-structured interviews, observations, and documentation from principals, teachers, and students. Data analysis followed the Miles and Huberman interactive model, while data validity was ensured through credibility, transferability, dependability, and confirmability criteria. The study concludes that the comprehensive implementation of the CFS program significantly contributes to establishing a positive school climate that supports students’ safety, comfort, and optimal learning. Keywords: Child-Friendly School, Creating a Positive, School Climate Abstrak: Penelitian ini bertujuan untuk mengkaji implementasi program Sekolah Ramah Anak (SRA) dalam mewujudkan iklim sekolah yang positif di SMPN 22 Mataram. Fokus penelitian mencakup tiga aspek utama: perencanaan, pelaksanaan, dan evaluasi program SRA. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara semi terstruktur, observasi, dan dokumentasi dari kepala sekolah, guru, dan siswa. Analisis data mengikuti model interaktif Miles dan Huberman, sedangkan keabsahan data dijamin melalui kriteria kredibilitas, transferabilitas, dependabilitas, dan konfirmabilitas. Penelitian ini menyimpulkan bahwa implementasi program SRA yang komprehensif berkontribusi signifikan dalam menciptakan iklim sekolah yang positif yang mendukung keamanan, kenyamanan, dan pembelajaran optimal bagi siswa. Kata Kunci: Sekolah Ramah Anak, Iklim Sekolah, Implementasi Program.